MO265: Patients with Alport Syndrome from the Radar Registry: A Natural History Study. (3rd May 2022) - Liu, Shiguang; Lin, Julie; Pitcher, David; Neil Turner, Andrew; Gale, Daniel
Abstract: BACKGROUND AND AIMS: Alport Syndrome (AS) is the second most common genetic kidney disease and results from mutations in COL4A3, A4 or A5 genes. It is characterized by glomerulonephritis, CKD, hearing loss, and ocular lens defects. Estimated incidence is ∼ 1 in 50 000 live births with prevalence of 1 in 5000–10 000. About 80% patients reach ESKD by age 35 years. The UK Alport Registry, part of the National Registry of Rare Kidney Diseases (RaDaR), performs on-going collection of longitudinal data of AS patients. The aims of this study were to characterize demographic and lab data of AS patients and determine the proportion of AS patients at risk for rapid kidney function decline. METHOD: Eligible patients had a clinical, histological or genetic diagnosis of 'Alport syndrome' or 'thin basement membrane nephropathy' by their physician and provided informed consent. Some data were entered manually, but most routine test results were collected by automatic link between RaDaR and renal IT systems. eGFR was calculated using CKD-EPI Cr equation without race adjustment (2021) or Schwartz equation for subjects ≤16 years of age at time of Cr measurement. For eGFR slope calculations, a minimum of four measurements over at least 2 years were required to be included in this analysis; subjects were censored if they reached ESKD, defined as maintenance dialysis, transplant, or ≥ 2 consecutive eGFR measurements of <15 mL/min/1.73 m 2 . Data are presented as percentages for categorical variables and mean ± SD for continuous variables. RESULTS: Between 4 January 2013 and 29 November 2021, 887 patients were recruited. See Table 1 for summary of data stratified by age groups. Overall, 52% male versus 48% female, and in those with genotyping data, 54% had X-linked AS with a mean age of 25.8 years at diagnosis and a mean age of proteinuria onset of 29.6 years. Clinically meaningful Stage 2 CKD was already present at time of diagnosis (mean eGFR 72.7 mL/min/1.73 m 2 ) in many of those ≥ 18 years of age. A total of 43% of this AS cohort have reached ESKD, at a mean age of 32.8 years. While 37% were on ACEi and 20% on ARB medications, only 4% were on dual RAAS blockade therapy. About 50% had documentation of eGFR loss ≥4 mL/min/1.73 m 2 per year, 29% had UPCR > 2 g/g, and 50% of those age ≥ 18 years had reached ESKD. The proportion of patients with ≥1 risk factor for rapid progression of kidney failure (defined as eGFR decline ≥ 4 mL/min/1.73 m 2 per year, UPCR > 2 g/g, UACR > 1 g/g or male 18–23 yrs with eGFR < 90 mL/min/1.73 m 2 based on ATHENA natural history study) was 41%. CONCLUSION: Demographic and genetic characteristics of AS patients in the RaDaR registry are generally comparable with previously reported data. Approximately 50% had eGFR decline ≥ 4 mL/min/1.73 m 2 per year and 41% of patients had exhibited ≥ 1 risk factor for future rapid progression of kidney disease. Results should be interpreted with caution, however, in light of the considerable amount of missing data in a number of the analyses. On-going data collection in this open cohort should allow for further insights on the natural history over time as well as identify AS patients for potential enrollment into clinical trials.